2012
DOI: 10.1152/ajprenal.00198.2011
|View full text |Cite
|
Sign up to set email alerts
|

Hypotonic stress upregulates β- and γ-ENaC expression through suppression of ERK by inducing MKP-1

Abstract: We investigated a physiological role for ERK, a member of the MAPK family, in the hypotonic stimulation of epithelial Na(+) channel (ENaC)-mediated Na(+) reabsorption in renal epithelial A6 cells. We show that hypotonic stress causes a major dephosphorylation of ERK following a rapid transient phosphorylation. PD98059 (a MEK inhibitor) increases dephosphorylated ERK and enhances the hypotonic-stress-stimulated Na(+) reabsorption. ERK dephosphorylation is mediated by MAPK phosphatase (MKP). Hypotonic stress act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…The level of phosphorylation of ERK1/2 is determined by a balance between the rate at which ERK is phosphorylated by kinases, in particular PKC-␦, and the rate at which it is dephosphorylated by phosphatases, in particular MKP. Changes in activity of MKP can alter ENaC functional channel density (40), and increases in cytosolic ROS inhibit MKP (5,31). Therefore, we investigated the effect of an MKP inhibitor on ENaC activity in wild-type and knockout cells.…”
Section: Less Absorptionmentioning
confidence: 99%
“…The level of phosphorylation of ERK1/2 is determined by a balance between the rate at which ERK is phosphorylated by kinases, in particular PKC-␦, and the rate at which it is dephosphorylated by phosphatases, in particular MKP. Changes in activity of MKP can alter ENaC functional channel density (40), and increases in cytosolic ROS inhibit MKP (5,31). Therefore, we investigated the effect of an MKP inhibitor on ENaC activity in wild-type and knockout cells.…”
Section: Less Absorptionmentioning
confidence: 99%
“…DUSPs have been implicated as major modulators of signaling pathways affecting various physiological processes (11). A recent study showed that hypotonic stress stimulates ␤-epithelial sodium channel (ENaC) and ␥-ENaC mRNA expression through suppression of ERK by inducing MKP-1 (28). DUSP6, also known as MAP kinase phosphatase 3 (MKP-3), is specifically responsible for ERK1/2 dephosphorylation (1, 26).…”
mentioning
confidence: 99%
“…Both lack of effect [64] and a positive effect of JNK1/2 [55] on NFAT5 have been reported. Like the effect on p38, hypotonicity also increases phosphorylation of ERK1/2 in human keratinocytes [73] , mIMCD3 cells [77] , renal epithelial A6 cells [72] , although inhibition of ERK by hypotonic stress in A6 cells was also reported [78] . Therefore, the mechanism for how ERK1/2 contributes to tonicity-dependent activation of NFAT5 remains to be elucidated.…”
Section: Potential Clinical Significance Of This Reviewmentioning
confidence: 89%